2004
DOI: 10.1111/j.1365-2222.2004.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone propionate aqueous nasal spray does not influence the recurrence rate of chronic rhinosinusitis and nasal polyps 1 year after functional endoscopic sinus surgery

Abstract: This placebo-controlled study does not show that treatment with FPANS up to 1 year after FESS had a positive effect compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(127 citation statements)
references
References 17 publications
0
125
1
1
Order By: Relevance
“…All studies showed a significant benefit from INCS therapy compared with placebo, with the exception of three that did not find a statistically significant difference. 5,17,21 Dijkstra et al, 17 had a high withdrawal rate (64-70%) that may explain the lack of a significant difference. Rotenberg et al 21 published a high-quality study that found no effect from budesonide treatment in comparison with placebo in Samter's triad patients.…”
Section: Qualitative Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…All studies showed a significant benefit from INCS therapy compared with placebo, with the exception of three that did not find a statistically significant difference. 5,17,21 Dijkstra et al, 17 had a high withdrawal rate (64-70%) that may explain the lack of a significant difference. Rotenberg et al 21 published a high-quality study that found no effect from budesonide treatment in comparison with placebo in Samter's triad patients.…”
Section: Qualitative Analysismentioning
confidence: 94%
“…Fifteen percent (n ϭ 274, 2/13) of studies were at high risk of incomplete outcome data with an attrition rate of 38% 15 and up to 70%. 17 Overall reporting bias assessment was considered as low risk (85%). Just 15% (n ϭ 270; 3/13 [18][19][20] ) of included studies were at high risk of selective reporting.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Three trials used a direct sinus delivery technique whereby the drug was instilled directly into the sinus through a sinusotomy tube in one study, 39 intrasinus lavage in one study, 63 and postoperative nasal irrigation in one study. 64 Thirty trials delivered the topical steroid via a nasal spray, 17 …”
Section: Figure 3 Meta-analysis Of Topical Steroid Versus Placebo Inmentioning
confidence: 99%
“…The literature contains a number of different findings concerning the use of nasal steroid spray after ESS. Dijkstra et al [14] used a doubleblinded randomized trial to assess the use of fluticasone propionate in reducing polyposis recurrence after ESS. The conclusion of the study was that the steroid did not have any beneficial effect on disease recurrence.…”
Section: Discussionmentioning
confidence: 99%